2019
DOI: 10.1016/j.ajog.2019.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Society for Maternal-Fetal Medicine (SMFM) Consult Series #48: Immediate postpartum long-acting reversible contraception for women at high risk for medical complications

Abstract: The Society of Family Planning (SFP) endorses this document. The American College of Obstetricians and Gynecologists (ACOG) supports the value of this clinical document as an educational tool; February 2019. Reproductive planning is essential for all women and most important for those with complex health conditions or at high risk for complications. Pregnancy planning can allow these high-risk women the opportunity to receive preconception counseling, medication adjustment, and risk assessment related to healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 65 publications
(67 reference statements)
0
17
0
Order By: Relevance
“…23 We found that nearly one in five deliveries (19.1%) in Mexico were to women with high-risk pregnancies or deliveries. Our definition of high risk is supported by the Society of Maternal Fetal Medicine 6 and previous research which has used a binary classification as the basis for their analysis. 21 Our proportion of high-risk pregnancies or deliveries is comparable to a US cohort studied in 2011 where 24% of women had a prepregnancy chronic disease, classifying them as high risk.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…23 We found that nearly one in five deliveries (19.1%) in Mexico were to women with high-risk pregnancies or deliveries. Our definition of high risk is supported by the Society of Maternal Fetal Medicine 6 and previous research which has used a binary classification as the basis for their analysis. 21 Our proportion of high-risk pregnancies or deliveries is comparable to a US cohort studied in 2011 where 24% of women had a prepregnancy chronic disease, classifying them as high risk.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] Specific counselling about the health effects of high-risk pregnancies, medical comorbidities and IPI should be standard to improve maternal health outcomes. 6…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 2 , 3 , 14 The study's primary outcome focused on Tier 1 plan and uptake of contraception on the basis of the American College of Obstetricians and Gynecologists (ACOG) and SMFM guidance to offer Tier 1 contraception to the most high-risk pregnancies given the low failure rate. 2 , 22 However, it is important to note that Tier 2 and 3 methods are safe and reliable methods, with typical-use 1-year failure rate ranging from 6% to 28% depending on the method. 20 This study included cardiovascular conditions with contraindications to estrogen-containing contraception and a heterogeneous group of providers with different levels of training in complex contraception counseling; therefore, we did not include Tier 2 methods uptake within the primary outcome.…”
Section: Methodsmentioning
confidence: 99%
“…1,2 Women with opioid use disorder are at 2 to 3 times greater risk for unintended pregnancy than the general population, [3][4][5] with current estimates indicating the unintended pregnancy rate in women with opioid use disorder is over 75% [5][6][7][8][9] (Table 1). Maternal substance use disorder, which includes drug or alcohol use, is associated with an increased risk for pregnancy-related morbidity 10 and neonatal abstinence syndrome (NAS), a condition that occurs when an infant experiences physical withdrawal symptoms due to exposure to maternal medication or drug use, most commonly opioids, before birth. The incidence of NAS in the United States increased over 5-fold between 2004 and 2014, from 1.5 to 8.0 per 1000 births.…”
mentioning
confidence: 99%